STUDENTS VIEW ON VOCABULARY ENHANCEMENT THROUGH LISTENING TO ENGLISH SONGS ON SPOTIFY - Aurora, Syavina Syahla Puteri; Fiftinova, Fiftinova (English Community Journal, 2025)
This study explores how English and non-English students perceive vocabulary enhancement through listening to English songs on Spotify. A total of 175 students, comprising 56 English majors and 119 non-English majors, participated in the research. Data were collected through a structured questionnaire, which employed Likert-scale indicators to measure students’ attitudes, strategies, and challenges, and semi-structured interviews that allowed participants to elaborate on their experiences. The analysis employed a qualitative descriptive approach, enabling the researchers to identify recurring patterns across both groups. The findings reveal that English majors adopted more strategic and academic approaches, such as analyzing lyrics and applying new words contextually, whereas non-English majors engaged more casually yet still benefited from repeated exposure and emotional engagement with music. Spotify’s distinctive features, particularly real-time lyrics, replay options, and playlist customization, were reported as highly supportive of vocabulary acquisition. Nonetheless, challenges such as fast tempo, unclear pronunciation, and idiomatic expressions remained obstacles, especially for English majors. Overall, the study highlights that Spotify, as a digital music platform, offers a flexible, accessible, and engaging medium for vocabulary learning, making it a valuable complementary tool for English as a Foreign Language (EFL) learners.